Pengaruh Pendidikan Kesehatan dengan Media Booklet Terhadap Pengetahuan, Sikap dan Tindakan Ibu Tentang Stimulasi Perkembangan Anak Usia Pra Sekolah di Wilayah Kerja Puskesmas Lubuk Buaya Kota Padang - Melda Saputri; Eva Chundrayetti; Deswita Deswita (Universitas Batanghari Jambi, 2021)
Children are the next generation of the nation, so it takes children with good quality in order to achieve a quality future of the nation. The reality is that low and middle income countries cannot realize the full development potential of children. Appropriate stimulation is needed such as with booklet media so that children develop well. This research is a quantitative study using the